Facile colorimetric detection of human chorionic gonadotropin based on the peptide-induced aggregation of gold nanoparticles. Issue 1 (16th October 2014) - Chang, Chia-Chen; Chen, Chen-Yu; Chen, Chie-Pein; Lin, Chii-Wann
Abstract : A facile and rapid optical detection method of human chorionic gonadotropin (hCG) was developed by using the hCG-binding peptide and the anti-aggregation of gold nanoparticles (AuNPs). Abstract : The human chorionic gonadotropin (hCG) assay for ectopic pregnancy is typically conducted using an enzyme immunoassay (EIA); however, EIA is complicated and time-consuming. Herein, we developed a simple, rapid and sensitive colorimetric assay for hCG based on the anti-aggregation of unmodified gold nanoparticles (AuNPs). The introduction of positively charged hCG-specific peptides into an AuNP solution causes the aggregation of the AuNPs, resulting in a color change from red to blue. When hCG is present, peptide/hCG complexes are formed, thus inhibiting the peptide-induced AuNP aggregation. The dynamic range for hCG detection ranged from 50 to 1000 mIU mL −1, with a detection limit of 25 mIU mL −1 . Additionally, this colorimetric sensor was successfully evaluated with serum samples spiked with hCG, demonstrating its ability to be used for the onsite monitoring of hCG.